2022
DOI: 10.3389/fneur.2022.781031
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulated Expression of Interferon-Gamma, Interleukin-6 and Tumor Necrosis Factor-Alpha in the Endolymphatic Sac of Meniere's Disease Suggesting the Local Inflammatory Response Underlies the Mechanism of This Disease

Abstract: BackgroundImmune mediated inflammatory changes affecting the endolymphatic sac (ES) may underlie the pathology of Meniere's disease (MD). The aim of the present study was to explore the differentially expressed cytokines in ES luminal fluid (ELF) of patients with MD, and the correlation between the expression of cytokines in the ELF with that in the serum was determined by quantitatively analyzing the cytokines in human ELF and serum.MethodsHuman ELF, serum and ES tissues were collected from patients with unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Animal studies have shown that the dark cells presented in the ES of guinea pigs had a considerable secretory ability, 22 and the hyperactivity of the cells in the ES of Lewis rats could be induced by immune reactivity, leading to an increase in endolymph secretion in ES 23 . More importantly, the ES is known to be the “source” of inner ear immune response, 24 and the abnormal immune response was consistently reported in the ES of patients with MD 25–27 . As a result, when the ES was attacked by the allergic reaction, 28 viral or bacterial infection, 29 autoimmunity, 30 otitis media‐induced inflammatory products and toxins, 31 the repeated inflammatory response may have the potential to induce the hypersecretion of endolymph in these normoplastic eESs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown that the dark cells presented in the ES of guinea pigs had a considerable secretory ability, 22 and the hyperactivity of the cells in the ES of Lewis rats could be induced by immune reactivity, leading to an increase in endolymph secretion in ES 23 . More importantly, the ES is known to be the “source” of inner ear immune response, 24 and the abnormal immune response was consistently reported in the ES of patients with MD 25–27 . As a result, when the ES was attacked by the allergic reaction, 28 viral or bacterial infection, 29 autoimmunity, 30 otitis media‐induced inflammatory products and toxins, 31 the repeated inflammatory response may have the potential to induce the hypersecretion of endolymph in these normoplastic eESs.…”
Section: Discussionmentioning
confidence: 99%
“…23 More importantly, the ES is known to be the "source" of inner ear immune response, 24 and the abnormal immune response was consistently reported in the ES of patients with MD. [25][26][27] As a result, when the ES was attacked by the allergic reaction, 28 viral or bacterial infection, 29 autoimmunity, 30 otitis media-induced inflammatory products and toxins, 31 the repeated inflammatory response may have the potential to induce the hypersecretion of endolymph in these normoplastic eESs. By contrast, the atrophic eESs determined in the present study showed a much smaller eES lumen with a vascular deficiency in its medial wall or an occluded ES lumen, suggesting the function of these eESs might be deteriorated due to their structural lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines, such as interleukin-1β (IL-1β), have been implicated in a wide variety of middle and inner ear conditions, including MD 12 , 56 , 57 . Consistently, we found that an increasement of IL-1β both in plasma and VEO of MD patients.…”
Section: Discussionmentioning
confidence: 99%
“…From the cytokines quanti ed in this study, we had observed increased levels of IL-8, TNFα, IL-4, IL-1α, MCP-1, and MIP1β in MD patients and IL-10, IL-1β, IL-6 in MDH patients. A study using endolymphatic sac luminal uid (ELF) and serum from MD patients and acoustic neuroma patients found signi cant differences in the expression of IL-6 and TNFα in ELF, but no differences were found in the serum (47). Moreover, increased levels of IL-4 and IL-10 have been found in the serum of MD patients when compared to controls (22,45).…”
Section: Discussionmentioning
confidence: 99%